Mating type distribution, fertility and pathogenicity of rice isolates of Magnaporthe grisea in four rice growing regions of India - and S.S.GNANAMANICKAM1, V. BRINDHA PRIY ADARISINI, G. VIJI (Indian Phytopathology, 2002)
One hundred monoconidial isolates of M. grisea, pathogenic to rice were obtained from 4 states of India, and were evaluated for perithecial production by crossing with known tester strains of the pathogen. Twenty-seven isolates produced perithecia but in 26 of them, the perithecia were barren without asci and ascospores. Ascospores were produced only in one of the fertile crosses which involved the rice isolate of M. grisea IN476.2.3 (from Kerala). Both mating types, Mat 1-1 (24 isolates) and Mat 1-2 (3 isolates) were found in this population. However, only one mating type was found in any one site or geographical rice growing region. From the fertile cross between M. grisea isolate IN476.2.3 and tester strain KA-9 (pathogenic to finger millet), 8recombinant ascospores were isolated and were evaluated for pathogenicity on a cultivar of finger millet and 3 cultivars of rice. Four of the 8 ascospores infected both finger millet and rice while the parents infected either finger millet or rice thusexhibiting distinct patterns of virulence and host range.